Outpatient Parenteral Antimicrobial Therapy With Ceftolozane/Tazobactam via Continuous Infusion for Multidrug-Resistant Pseudomonas aeruginosa Osteomyelitis - Álvarez Otero, Judith (Open Forum Infect Dis, 2020)
We present a case of Pseudomonas aeruginosa osteomyelitis treated with surgery and antibiotic therapy with ceftolozane-tazobactam in continuous infusion at home using an elastomeric pump. We discuss the use of ceftolozane-tazobactam in continuous infusion administered at home as an effective alternative for the treatment of multidrug-resistant Pseudomonas aeruginosa osteomyelitis.